THE LINGUODIDACTIC METHODS OF FAMILIARIZING STUDENTS WITH FOREIGN CULTURAL CONCEPTS - Prozhohina, I. (Linguistic and Conceptual Worldviews, 2019)
Modern philological education provides a deep introduction to the national culture as well as the national mentality of native speakers of a particular language. Linguistic conceptology is an academic discipline serving this purpose. There are some tutorials created by Taras Shevchenko National Uni- versity of Kyiv professors I.O. Holubovska, O.S. Snytko, N.V. Slukhay, and others, that are dedicated to this subject matter. However, the linguodidactic aspect of linguistic conceptology, especially for training foreigners, has not been investigated yet. This article deals with some of the linguodidactic methods concerning familiarizing foreign students with Russian cultural concepts. These methods are used by the author of this article in an academic course “The Russian Language and Cultural Con- cepts” which is a part of the educational program “The Russian Language and Literature” for foreign students of master’s degree in the Institute of Philology. A teacher’s intention is to provide foreign students with some information concerning national peculiarities of Russian linguocultural concepts. Familiarizing students with cultural concepts must include three pillars: an image, a conceptual component and a value dimension which is the most important one. The linguodidactic methods for this purpose are: visualization of information using heuris- tic approach; insight into metaphorical traits of a concept; use of idiomatic expressions etc.; use of synonyms; explanation of word etymology and ascertaining of derivational links; experimental data received through psycholinguistics methods; cognitive analysis of poets’ and writers’ sentences about a topic. Specific pieces of Russian cultural concepts (УЮТ, ДУША, ИНТЕЛЛИГЕНЦИЯ, НЕПРИКАЯННЫЙ, МАЯТЬСЯ and some others) are good examples of these methods usage. Choos- ing a method depends on concept peculiarities. It is proved that the heuristic method is the most eﬀec- tive one, considering the necessity of development master’s general and special competences.